2016
DOI: 10.1111/nmo.12916
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics of the pharyngeal event‐related potential in healthy subjects and older patients with oropharyngeal dysfunction

Abstract: Older people present a decline in pharyngeal sensory function, more severe in older patients with OD. This sensory impairment might be a critical pathophysiological element and a potential target for treatment of swallowing dysfunction in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 58 publications
10
52
0
Order By: Relevance
“…Aviv et al [7] found a positive correlation between impaired laryngopharyngeal sensitivity and aspiration in patients with stroke. In contrast, we found no significant differences in pharyngeal sensory thresholds between PSD and PSnD, similar to previous findings using the same technique in an elderly population [6]. In addition to methodological differences (depending on distinct receptor activation in pharyngeal mucosa due to air puff vs. electrical stimulation), discrepancies may be explained by the fact that, in the study of Aviv et al [7], patients were in the acute phase of stroke, the majority located in the brainstem (66.7%), whereas we recruited chronic post-stroke patients, over 80% of whom were total anterior circulation infarct/partial anterior circulation infarct.…”
Section: Pharyngeal Sensitivitysupporting
confidence: 92%
See 1 more Smart Citation
“…Aviv et al [7] found a positive correlation between impaired laryngopharyngeal sensitivity and aspiration in patients with stroke. In contrast, we found no significant differences in pharyngeal sensory thresholds between PSD and PSnD, similar to previous findings using the same technique in an elderly population [6]. In addition to methodological differences (depending on distinct receptor activation in pharyngeal mucosa due to air puff vs. electrical stimulation), discrepancies may be explained by the fact that, in the study of Aviv et al [7], patients were in the acute phase of stroke, the majority located in the brainstem (66.7%), whereas we recruited chronic post-stroke patients, over 80% of whom were total anterior circulation infarct/partial anterior circulation infarct.…”
Section: Pharyngeal Sensitivitysupporting
confidence: 92%
“…Although delay of earlier pSEP peaks (N1/P1) is probably related to conduction slowing through the afferent pathway at the stroke site, delay of later peaks (N2/P2) also suggests impaired integration of sensory inputs. ERP studies have reported an altered pharyngeal sensory pathway in dysphagic elderly people and in Parkinson's disease [6,19]. The inverse correlation that we found between N2/P2 amplitude and LV closure time indicates that impaired sensory integration of pharyngeal inputs is associated with impaired safety of swallowing.…”
Section: Pharyngeal Sensory Pathwaymentioning
confidence: 44%
“…Older people and patients with neurological diseases suffering from OD present decreased oropharyngeal sensitivity . Reduced sensory input contributes to impaired motor response .…”
Section: Discussionmentioning
confidence: 99%
“…While TRP stimulants increased bolus velocity and reduced swallow response times, Older people and patients with neurological diseases suffering from OD present decreased oropharyngeal sensitivity. 16 Reduced sensory input contributes to impaired motor response. 17,18 Thus, sensory impairment is a potential target for treatment of swallowing dysfunction in older patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation